Can Elected Minority Representatives Affect Health Worker Visits? Evidence from India - Elizabeth Kaletski; Nishith Prakash (Institute for the Study of Labor (IZA), 2014)
This paper examines the relationship between elected minority representatives, Scheduled Castes and Scheduled Tribes, and health worker visits in rural India. We estimate the effect of minority representation on the frequency of visits to villages by health workers by exploiting the state variation in the share of seats reserved for the two groups in state legislative assemblies mandated by the Constitution of India. Using data from state and village level surveys on fifteen major Indian states, we find that Schedule Tribe representatives increase the frequency of visits by both doctors and mobile medical units. On the other hand, Scheduled Caste representatives have a tendency to decrease the frequency of visits by mobile medical units. Potential explanations for the differential impact of SC and ST representatives are also explored, including geographic isolation, support for the Congress Party, and relative population shares.
Keywords: I18; I38; J15; 330; health; minorities; affirmative action; public goods provision; India